Branding & Product Knowledge Parfum Ramah Wudhu Serta Halal Sebagai Upaya Peningkatan Kewirausahaan Mahasiswa dan Produksi UKM - ULFAH, INDAR FAUZIAH; Widowati Hermajiwandini, Chandra Murti Dewi; Priyati, Rini Yayuk; Pradana, Hasta Dwi; Mardoni, Yosi; Nisa Purnamasari; Rina Amelia (Universitas Terbuka, 2024)
The main problem faced by Small and Medium Enterprises (SMEs) in the cosmetics and perfume sector is the lack of a deep understanding of product knowledge aspects and halal product standards, especially in the context of the majority Indonesian Muslim market. This community service activity (PKM) aims to increase the entrepreneurial capacity of students and partner SMEs through intensive training on branding, product knowledge, and halal certification processes for ablution-friendly perfume products. The method of implementing activities includes three stages: (1) Socialization and education about the importance of halal certification and the concept of ablution-friendly perfume; (2) Technical training on the preparation of brand identity and digital marketing strategies; and (3) Direct assistance in improving the quality of SME Partner products. The results achieved were a significant increase in the understanding of participants (students and SMEs) by 35% regarding halal and branding aspects. In addition, SME Mitra has successfully identified and reformulated the Unique Selling Proposition of their products, namely perfumes that meet the criteria of 'ablution-friendly'. This activity succeeded in creating synergy between academics and business actors in producing competitive products in the halal market.